Rozie Times: Tuanku Agong proclaims UiTM Hospital as Al-Sultan Abdullah Hospital / Galeri Seni Tuanku Nur Zahirah - Universiti Teknologi MARA, Galeri Seni Tuanku Nur Zahirah (GESTURZ) (Galeri Seni Tuanku Nur Zahirah, UiTM, 2022)
Rozie TImes 3 continues chronicling the events and achievements of UiTM alongside Datuk Rozie, now past her 300th day in office. From the articles we learn of numerous MoUs signed and partnership forged, charitable and social enterprises undertaken, appointments and accomplishments made, all communicated in her conversational style. Once again her love and price for Keluarga UiTM were evidenced, as she jotted down the names and personally thanked individuals from various faculties, departments, centres, offices, organisations, and communities that have made an impression. Rozie Times shares the essence of the Vice-Chancellor's distinctive leadership and viewpoints.